UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH DI KELAS V SD NEGERI 008 BANJAR NAN TIGO KECAMATAN INUMAN - Rabiah Rabiah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research begins from the results of learning mathematics students class V of SD Negeri 008 Banjar NanTigo is still very low. This study aims to improve the learning outcomes of mathematics on the subject offractional addition operations and mixed count operations. From the data analysis, there was an increase ofboth teacher activity, student activity, and student learning result. The activity of teacher in the first cycle I was66.67% (enough) and at the second meeting increased by 4.16% to 70.83% (good). In the second cycle ofmeeting 3 it increased by 12.5% from 83.33% (very good) to 91.67% (very good). Judging from the studentactivity also increased from the first cycle I meeting was 62.5% (enough) and at the 2nd meeting increased by4.17% to 66.67% (enough). In the second cycle of meeting 3 it increased by 12.49% from 66.67% (sufficient) to79.16% (good) and at 4th meeting increased by 8.34% from 79.16% (good) to 87.5% (very good). The averagebaseline score of 55.5 increased to 70.35 in cycle I of the 14.5 points increase and then in cycle II increased to80.12 on the second cycle, the increase was 9.77 points. From the data analysis there is an increase both fromteacher activity, student activity, and student learning outcomes. It can be concluded that the enforcement of theproblem-based learning model can improve the learning outcomes of students mathematics class V of SD Negeri008 Banjar Nan Tigo.